Verba Turunan dalam Bahasa Melayu Riau Kepulauan Meranti - Aryananda, Tegar Rizki; Alber, Alber (Universitas Negeri Semarang, 2022)
This study aims to describe the process of affixing, reduplication, and compounding of derived verbs in the Malay language of the Meranti Islands Regency. This research is a field research that uses a qualitative approach with an ethnographic method. Data were collected through observation, interview, recording, and face-to-face conversation techniques. Based on the research of derivative verbs in Riau Malay, Meranti Islands Regency, it can be concluded that verbs have a big role in forming a sentence. The process of deriving verbs in Riau Malay, Meranti Islands Regency is also very productive. This can be seen from the various processes of verb derivation such as affixation, reduplication, and compounding. The types of affixes in this study consisted of the prefixes me-, mem-, me-, pe-, be-, di-, te-, suffixes -kan and -i, and the confixes di-kan, ter-kan, and per-kan. In Riau Malay, Meranti Islands Regency, it was found that there were 24 data affixation processes, 14 data reduplication processes, and 8 data compounding processes.